Accuracy of deployment of the Relay non-bare stent graft in the aortic arch. (22nd December 2018) - Riesterer, Tatjana; Beyersdorf, Friedhelm; Scheumann, Johannes; Berezowski, Mikolaj; Schröfel, Holger; Kondov, Stoyan; Czerny, Martin; Rylski, Bartosz
Abstract: OBJECTIVES: To minimize the complications with thoracic endovascular aortic repair (TEVAR), a new stent graft with no bare ends was developed, namely the Relay non-bare stent (NBS). We hypothesized that the new features of the NBS graft would enable highly accurate deployment and fewer complications. The aim of this study was to analyse the quality of the Relay NBS with respect to its landing precision. METHODS: Relying on computed tomography angiographs, we evaluated the distance between the stent graft and the target vessel in the proximal landing zone (before and after the intervention as well as the mid-term results). Seventy-eight patients with thoracic aortic pathologies were included. Median computed tomography angiograph follow-up was 16 months. RESULTS: The stent graft was deployable≤ 5 mm from the target vessel in 64 (82%) patients; in 14 (18%) of them, the distance to the target vessel was >5 mm. According to the last follow-up computed tomography angiograph, in 35 (55%) patients, the distance to the target vessel was≤ 5 mm and in 29 (45%) patients, it was >5 mm. There was no endoleak type Ia immediately after TEVAR or during the follow-up period. A substantial bird beak phenomenon was observed in 3 (4%) and 7 (11%) patients immediately after TEVAR and during the follow-up period, respectively. One patient had a retrograde dissection type A. CONCLUSIONS: The Relay NBS graft can be deployed accurately in the aortic arch in most patients. Retrograde aortic dissection type A seldom occurs after TEVAR using the Relay NBS graft. The distance between the NBS graft and the intended target vessel increases during the follow-up period.